Experimental testing of composite sandwich panels with different face sheets - Trombeva-Gavriloska, Ana; Lazarevska, Marijana; Cvetkovska, Meri (Centre for Evaluation in Education and Science (CEON/CEES), 2016)
An experimental tests performed on two series sandwich panels with composite face sheets differed by the type of the used matrix are presented in this paper. Using linear load in the middle of the span these sandwich panels were subjected on three points bending. The analysis was performed in order to evaluate the influence of the matrix type on the ultimate mechanical characteristics of the sandwich panels. Analyzing the F- δ behavior of the sandwich panels, as well the F-σ behavior of the composite face sheets the influence of the matrix type used in the composite face sheets has been evaluated.
Keywords: Composite sandwich panels, mechanical properties, experimental testing